Mainstreaming Kenya-Nursing Process in clinical settings: The case of Kenya - Miriam Carole Atieno Wagoro; Chris Podo Rakuom (Elsevier, 2015)
Background: Utilization of the nursing process in many low and middle income countries has been a challenge. In Kenya, nursing process was modified to operationalize its implementation and hence the name "Kenya-Nursing Process (Kenya-NP)". Purpose: The authors aim to publicize their experiences in mainstreaming nursing process in clinical settings in Kenya. Methodology: The Harris et al. (2012), Health Promotion Research Center dissemination framework has been used in mainstreaming Kenya-NP since the year 2010. Mainstreaming Kenya-NP involves two-weeks of training in theory followed by two months of supervised practice and a practical assessment. A certificate of competence is awarded to those who pass according to the set criteria. Results: Preliminary results indicate a positive change of attitude towards the nursing process among nurses and students. Mainstreaming nursing process has been strengthened by its adoption as the official framework for nursing practice in Kenya. Reports from the health sector reforms supervisory visits indicate some improvement in the quality of nursing care in hospitals that implement Kenya-NP especially in documentation. Significance: The authors anticipate that this article will be significant to nurse clinicians, educators and administrators who experience challenges in implementing nursing process in their countries. Additionally, nurse scholars could be interested in trying the modifications made in the structure and phases of the nursing process as well as administrative and policy integration used in mainstreaming the Kenya-NP to provoke further research. Conclusion: It is possible to mainstream a contextualized nursing process in clinical settings using a relevant knowledge dissemination framework.